Silence Out of Fear: A Case Study of the Spiral of Silence in Social Media Doxxing Victims - Ramadhani, Sansa Aldira; Khodari, Rifqi Taufiqurrohman; Ulfiah, Naily; Rosydawati, Aprilia (Jurnal Multidisiplin Indonesia, 2025)
This study examines the spiral of silence phenomenon experienced by doxxing victims on Indonesian social media. Doxxing, as a form of cyberbullying involving unauthorized disclosure of personal information, has generated significant psychological and social consequences for victims. Evidence indicates that 21.05% of fact-checkers have encountered intimidation and doxxing on digital platforms, while reports from AJI (Alliance of Independent Journalists) Indonesia document numerous content creators experiencing fear of expression following such digital attacks. The research employs a qualitative approach through case study methodology, incorporating in-depth interviews with four informants who experienced doxxing within the past two years. Findings reveal that victims endure emotional trauma manifested through fear, anxiety, and withdrawal from both online and offline social interactions. The fear of social isolation compels victims toward self-censorship by locking accounts, removing content, and restricting online activities. The internalization of fear occurs through perceptions that attacking groups possess superior strength, rendering silence a chosen defense mechanism. Victims' motivation to return to social media stems from social support provided by family, friends, and communities, alongside functional necessities in daily life. Adaptations implemented include communication self-regulation, modification of online identity through pseudonyms or anonymous accounts, and pursuit of emotional support from fellow victim communities. These findings confirm that doxxing not only violates individual privacy but also generates a broader spiral of silence effect, transforming digital communication dynamics from open dialogue arenas into repressive and surveillance environments.